Forest structure assessment of a rehabilitated forest - Kueh, Roland Jui Heng; Nik Ab. Majid, Nik Muhamad; Gandaseca, Seca; Ahmed, Osumanu Haruna; Jemat, Silvester; Ku, Melvin Kin Kin (Science Publications, 2011)
Problem statement: Forest structure assessment provides information on forest succession, dynamics, biodiversity and health which are important but only few information is available on rehabilitated forest. The objective of this study was to assess the forest structure of selected age stands at a rehabilitated forest situated in Universiti Putra Malaysia Bintulu Sarawak Campus, Sarawak, Malaysia. Approach: Four 20×20 m plots were established in stands planted in 1991, 1999, 2008 and an adjacent natural regenerating secondary forest (±22years) and all stands were measured for Diameter Breast Height (DBH) and height and identified. Results: Forest structural analysis showed better performance in the structural characteristics mainly the mean basal area (61%), mean Dbh (56%) and mean height (60%) of the trees as compared to the adjacent natural regenerating secondary forest. Conclusion: It can be concluded that after 18 years, rehabilitated forest using accelerating natural regeneration technique showed better structural dimension. This can help to promote the reforestation and restoration activities on degraded forest. Overall, rehabilitated forest areas have yet recovered in terms of size and height.